2015
DOI: 10.1002/2015jd023572
|View full text |Cite
|
Sign up to set email alerts
|

Potential sensitivity of warm season precipitation to urbanization extents: Modeling study in Beijing‐Tianjin‐Hebei urban agglomeration in China

Abstract: In this study, we investigated how different degrees of urbanization affect local and regional rainfall using high-resolution simulations based on the Weather Research and Forecasting Model. The extreme rainfall event of 21 July 2012 in Beijing was simulated for three representative urban land use distributions (no urbanization, early urbanization level of 1980, and recent urbanization level of 2009). Results suggest that urban modification of rainfall is potentially sensitive to urban land use condition. Rain… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
47
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 64 publications
(53 citation statements)
references
References 58 publications
5
47
1
Order By: Relevance
“…The detected causal relationships are further supported by the physical mechanism of regional climate modeling under different scenarios of land use changes, which makes the findings even more convincing. Therefore, our study is a further extension of existing studies (Kaufmann et al, ; Song et al, ; J. Wang et al, ; Y. J. Yang et al, ).…”
Section: Discussionmentioning
confidence: 58%
“…The detected causal relationships are further supported by the physical mechanism of regional climate modeling under different scenarios of land use changes, which makes the findings even more convincing. Therefore, our study is a further extension of existing studies (Kaufmann et al, ; Song et al, ; J. Wang et al, ; Y. J. Yang et al, ).…”
Section: Discussionmentioning
confidence: 58%
“…The CC of the observational and simulated daily precipitation in January was 0.76 and 0.8 in July, which meant that the simulation reflected various features well. In terms of the bias, the results from the observed values were higher than those from the simulation, which also appeared in Wang, Feng [16], who also noted why it was difficult to accurately simulate rainfall. This study focused on the difference in underlying surface changes affecting regional meteorology, and some model systematic errors can ultimately be offset by subtraction.…”
Section: Validation Of the Wrf Simulationmentioning
confidence: 86%
“…Because the vertical and horizontal air circulation were impacted, the precipitation decreased in this area. Because precipitation is a complex process, it is difficult to simulate its exact value [16]; however, LULC change is a factor that affects its trend.…”
Section: Discussionmentioning
confidence: 99%
“…The sharp decrease in relative humidity imposes a negative effect on the CAPE, which can negate and even overwhelm the promoting effects of urbanization on rainfall. Wang et al () partly explained the previous contradictory findings on the urban modification of rainfall. Nonetheless, it should be noted that most of these previous studies were based on the simulations of selected heavy rainfall cases and short‐term observational data, while few has examined the impact of urbanization on regional rainfall in a climatological sense.…”
Section: Introductionmentioning
confidence: 98%
“…Recent studies that focused on cities with high‐level urbanization situated in dry regions, such as the Beijing‐Tianjin‐Hebei metropolitan region, suggested that extensive urbanization could lead to a general reduction of regional rainfall (Feng et al, ; Guo et al, ; Wang et al, ; Zhang et al, , ; Zhong et al, ). Based on the analysis of rainfall data and numerical simulations for two selected heavy summer rainfall events, Zhang et al () revealed that the rapid urban expansion in Beijing is responsible for the reduction in summertime rainfall in the northeast areas of Beijing in the recent decades.…”
Section: Introductionmentioning
confidence: 99%